Pierre Robin sequence: Subdivision, data, theories, and treatment - Part 1: History, subdivisions, and data - Bütow, Kurt-W (Ann Maxillofac Surg, 2016)
CONTEXT: The disorder currently accepted as Pierre Robin syndrome/anomaly/sequence (PRS) has been plagued by controversy ever since initially being described. Controversy exists not only about the appropriate terminology and etiopathogenesis of the disorder but also about its management. Therefore, clinical findings and treatment outcomes of a large database of 266 PRS cases were compared with the current state of knowledge in scientific literature related to history, clinical description, diagnostic criteria, epidemiology, theories of oligohydramnios, mandibular catch-up growth, midfacial hyperplasia, and the timing of management. AIMS OF PART 1: Display disparities of the widely published subject of PRS that exist within the literature. SUBJECTS AND METHODS: A literature search related to diagnostic criteria was compared to findings of one of the largest PRS databases worldwide. RESULTS: Regarding diagnostic criteria two subdivisions, the Fairbairn–Robin triad (FRT) and the Siebold–Robin sequence (SRS) can be clearly distinguished. Both present with micrognathia and glossoptosis, the former with, the latter, however, without a palatal cleft. CONCLUSIONS: According to clear diagnostic criteria, PRS has to be subdivided in the future into FRT and SRS cases, as they may require different treatment approaches.